(untitled) (American International Journal of Education and Linguistics Research, 2018)
The study examined teachers’ workload and determined its implication on students’ academic performance in secondary schools in Akoko North East Local Government Area of Ondo State. Descriptive design of the survey type was adopted and a stratified random sampling was used to select 12 schools, which were 6 public and 6 private secondary schools, involving 132 participants who included 120 teachers and 12 principals. A self-constructed questionnaire titled “Teachers’ Workload and Student’s Academic Performance Questionnaire” (TWSAPQ), was administered. Five (5) hypotheses were tested using Pearson’s product moment correlation (PPMCC) and T-test at p<0.05 level of significance. The results showed that there was a negative correlation between teachers’ workload and students’ academic performance (r-cal= -0.420), and a disparity between teachers’ actual workload and workload policy standard (t-cal=27.219), also there was significant difference in teachers’ workload between public and private secondary schools (t-cal=2.364). The findings indicated that teachers’ workload is high in teaching activities (75.8%), data imputation (62.5%), and marking of students’ scripts (76.7%), .and impacted negatively on teachers’ instructional tasks performance and students’ academic performance. It is hereby recommended that the State Government and proprietors of private secondary schools should employ adequate number of qualified teachers to meet the workload standard for effective teaching, while learning facilities should be upgraded to enhance workload implementation and improve students’ academic performance in secondary schools.